Indole pyruvate decarboxylase gene regulates the auxin synthesis pathway in rice by interacting with the indole-3-acetic acid–amido synthetase gene, promoting root hair development under cadmium stress - Gulmeena Shah; Sajid Fiaz; Kotb A. Attia; Naeem Khan; Muhammad Jamil; Adeel Abbas; Seung Hwan Yang; Tu Jumin (Frontiers in Plant Science, 2022)
This research focused on cadmium (Cd), which negatively affects plant growth and auxin hemostasis. In plants, many processes are indirectly controlled through the expression of certain genes due to the secretion of bacterial auxin, as indole-3-acetic acid (IAA) acts as a reciprocal signaling molecule in plant–microbe interaction. The aim of current studies was to investigate responsible genes in rice for plant–microbe interaction and lateral root development due to the involvement of several metabolic pathways. Studies revealed that GH3-2 interacts with endogenous IAA in a homeostasis manner without directly providing IAA. In rice, indole-3-pyruvate decarboxylase (IPDC) transgenic lines showed a 40% increase in lateral roots. Auxin levels and YUCCA (auxin biosynthesis gene) expression were monitored in osaux1 mutant lines inoculated with Bacillus cereus exposed to Cd. The results showed an increase in root hairs (RHs) and lateral root density, changes in auxin levels, and expression of the YUCCA gene. B. cereus normalizes the oxidative stress caused by Cd due to the accumulation of O2− and H2O2 in osaux1 mutant lines. Furthermore, the inoculation of B. cereus increases DR5:GUS expression, indicating that bacterial species have a positive role in auxin regulation. Thus, the current study suggests that B. cereus and IPDC transgenic lines increase the RH development in rice by interacting with IAA synthetase genes in the host plant, alleviating Cd toxicity and enhancing plant defense mechanisms.